2013
DOI: 10.1186/1479-5868-10-11
|View full text |Cite
|
Sign up to set email alerts
|

Neighbourhood safety and leisure-time physical activity among Dutch adults: a multilevel perspective

Abstract: BackgroundSeveral neighbourhood elements have been found to be related to leisure-time walking and cycling. However, the association with neighbourhood safety remains unclear. This study aimed to assess the association of neighbourhood-level safety with leisure-time walking and cycling among Dutch adults.MethodsData were derived from the national health survey (POLS) 2006–2009, with valid data on 20046 respondents residing in 2127 neighbourhoods. Multilevel logistic regression models were used to examine the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
46
1
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 35 publications
2
46
1
1
Order By: Relevance
“…Recent single-country studies reported mixed findings on this topic. Studies in Brazil (Gomes et al, 2011), Japan (Inoue et al, 2011), and The Netherlands (Kramer et al, 2013) showed no association of safety from crime with walking for recreation, but results from Nigeria (Oyeyemi et al, 2012) and the USA (Evenson et al, 2012) supported an interpretation that crime is an important correlate of physical activity. It is possible that the present study was able to identify a significant association because data were gathered from diverse countries, thus expanding the range of variation.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Recent single-country studies reported mixed findings on this topic. Studies in Brazil (Gomes et al, 2011), Japan (Inoue et al, 2011), and The Netherlands (Kramer et al, 2013) showed no association of safety from crime with walking for recreation, but results from Nigeria (Oyeyemi et al, 2012) and the USA (Evenson et al, 2012) supported an interpretation that crime is an important correlate of physical activity. It is possible that the present study was able to identify a significant association because data were gathered from diverse countries, thus expanding the range of variation.…”
Section: Discussionmentioning
confidence: 95%
“…The finding of no association between safety from traffic and recreational walking is consistent with previous studies (Saelens and Handy, 2008; Sugiyama et al, 2012). A recent study in the Netherlands found traffic safety to be associated with recreational cycling but not with recreational walking (Kramer et al, 2013). It is possible that traffic safety is a construct consisting of several dimensions, such as traffic volume, speed, and facilities for protecting and separating pedestrians and cyclists from traffic.…”
Section: Discussionmentioning
confidence: 99%
“…A common pathway for both observed associations can be through social stressors. In childhood, exposure to social class related stressors may affect biological systems and thus health in the long-term36; in the neighbourhood level, high crime rates, for example, may increase smoking prevalence37 and low safety may decrease physical activity 38…”
Section: Discussionmentioning
confidence: 99%
“…Objective and perceived environment characteristics have been found to be associated with the likelihood of physical activity in high-income countries (Hoehner, et al, 2005, Baker, et al, 2008, Bedimo-Rung, et al, 2005, Roux, et al, 2007, Kramer, et al, 2013). Recent evidence identifying a relationship between physical activity and the built environment has also emerged from low and middle-income countries, suggesting widespread importance (Hallal, et al, 2012, Gomez, et al, 2010, Parra, et al, 2010, Parra, et al, 2011).…”
Section: Introductionmentioning
confidence: 99%